2009
DOI: 10.1128/ec.00252-08
|View full text |Cite
|
Sign up to set email alerts
|

Growth at High pH and Sodium and Potassium Tolerance in Media above the Cytoplasmic pH Depend on ENA ATPases in Ustilago maydis

Abstract: Potassium and Na؉ effluxes across the plasma membrane are crucial processes for the ionic homeostasis of cells. In fungal cells, these effluxes are mediated by cation/H ؉ antiporters and ENA ATPases. We have cloned and studied the functions of the two ENA ATPases of Ustilago maydis, U. maydis Ena1 (UmEna1) and UmEna2. UmEna1 is a typical K ؉ or Na ؉ efflux ATPase whose function is indispensable for growth at pH 9.0 and for even modest Na ؉ or K ؉ tolerances above pH 8.0. UmEna1 locates to the plasma membrane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 58 publications
3
43
0
1
Order By: Relevance
“…Drops of cell suspensions of three serial ten-fold dilutions were inoculated in the recorded media UmEna2 locates to the ER and is not involved in cellular Na ? efflux (Benito et al 2009). Unfortunately, we have not yet been able to express the PpENA2-GFP and PpENA3-GFP fusions in P. patens protoplasts, and we therefore do not know in which membranes PpENA2 and PpENA3 are expressed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Drops of cell suspensions of three serial ten-fold dilutions were inoculated in the recorded media UmEna2 locates to the ER and is not involved in cellular Na ? efflux (Benito et al 2009). Unfortunately, we have not yet been able to express the PpENA2-GFP and PpENA3-GFP fusions in P. patens protoplasts, and we therefore do not know in which membranes PpENA2 and PpENA3 are expressed.…”
Section: Discussionmentioning
confidence: 95%
“…or Na ? against their concentration gradients (Benito et al 2009;Idnurm et al 2009). At high pH, the DpH across the plasma membrane would drive H ?…”
Section: Introductionmentioning
confidence: 98%
“…Using fungal Ena-like proteins as queries in the U. maydis database, we identified gene um00204 that showed the highest homology. This gene encodes a protein that shares all the structural characteristics exhibited by Ena proteins, and accordingly was isolated [during the course of our study the same gene was identified and denominated as UmEna2 (Benito et al, 2009)]. Gene expression was evaluated by Northern hybridization in media supplemented with NaCl (0.4 M) or LiCl (0.003 M).…”
Section: Analysis Of the Expression Of Selected Genesmentioning
confidence: 99%
“…A recent report (18) has proposed the existence of two types of fungi in regard to Na ϩ tolerance: those tolerant to high Na ϩ contents in the cytoplasm, which include U. maydis, and those intolerant to high Na ϩ contents, which include the model yeast S. cerevisiae. However, in both types, vacuolar transport may play an important role in cation homeostasis.…”
Section: Vacuolar Transportmentioning
confidence: 99%
“…The Ena transporters, the main determinants of halotolerance in S. cerevisiae and probably present in most fungi (15,18,19), do not exist in flowering plants (85). Remarkably, two Na ϩ -ATPases in the moss Physcomitrella patens have been characterized (23) and at least one of them (PpEna1), appears to be functional as a sodium pump both in S. cerevisiae (23) and in planta (145).…”
mentioning
confidence: 99%